One-step nucleic acid amplification vs ultrastaging in the detection of sentinel lymph node metastasis in endometrial cancer patients - Kosťun, Jan; Pešta, Martin; Sláma, Jiří; Slunečko, Robert; Vlasák, Pavel; Bouda, Jiří; Novotný, Zdeněk; Topolčan, Ondřej; Kučera, Radek; Kulda, Vlastimil; Houfková, Kateřina; Berezovskiy, Denis; et al. (Journal of surgical oncology, 2019)
BACKGROUND AND OBJECTIVES: Utilisation of the one-step nucleic acid amplification (OSNA) molecular biology method for the detection of the metastatic involvement of sentinel lymph nodes (SLNs) in endometrial cancer (EC) patients. A comparison with histopathological ultrastaging and a description of the clinical consequences. METHODS: Surgically treated EC patients underwent detection of SLNs. Nodes greater than 5 mm were cut into sections 2-mm thick parallel to the short axis of the node. Odd sections were examined according to the OSNA method, while even ones according to an appropriate ultrastaging protocol. Nodes less than or equal to 5 mm were cut into halves along the longitudinal axis with one half examined according to the OSNA method and the other half by ultrastaging. RESULTS: Fifty-eight patients were included and 135 SLNs were acquired. Both ultrastaging and OSNA agreed on 116 results. According to the OSNA method, 20.69% more patients were classified into International Federation of Gynecology and Obstetrics (FIGO) stage III. When comparing the results of the OSNA method to the conclusions of ultrastaging as a reference method, sensitivity of 90.9%, specificity of 85.5% and concordance of 85.9% were attained. CONCLUSIONS: The results of the OSNA method showed a higher frequency of detection of micrometastases and included 20.69% more patients into FIGO stage III.
Keywords: Aged; nukleové kyseliny; Neoplasm Micrometastasis; Survival Rate; Aged, 80 and over; nádory endometria; peroperační doba; prognóza; mikrometastázy; lidé; lidé středního věku; senioři; ženské pohlaví; Nucleic Acid Amplification Techniques; Keratin-19; Endometrial Neoplasms; Biomarkers, Tumor; Intraoperative Period; Sentinel Lymph Node; Female; Cystadenocarcinoma, Serous; sentinelová uzlina; serózní cystadenokarcinom; Lymphatic Metastasis; Adult; biopsie sentinelové lymfatické uzliny; Follow-Up Studies; Middle Aged; adenokarcinom z jasných buněk; senioři nad 80 let; keratin-19; Sentinel Lymph Node Biopsy; míra přežití; Humans; lymfatické metastázy; techniky amplifikace nukleových kyselin; dospělí; následné studie; Prognosis; Adenocarcinoma, Clear Cell; nádorové biomarkery; Nucleic Acids